2007
DOI: 10.1128/jvi.02006-06
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Maximal Inhibition in Phenotypic Susceptibility Assays Indicates that Viral Strains Resistant to the CCR5 Antagonist Maraviroc Utilize Inhibitor-Bound Receptor for Entry

Abstract: Maraviroc is a CCR5 antagonist in clinical development as one of a new class of antiretrovirals targeting human immunodeficiency virus type 1 (HIV-1) coreceptor binding. We investigated the mechanism of HIV resistance to maraviroc by using in vitro sequential passage and site-directed mutagenesis. Serial passage through increasing maraviroc concentrations failed to select maraviroc-resistant variants from some laboratory-adapted and clinical isolates of HIV-1. However, high-level resistance to maraviroc was se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

25
481
3
4

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 323 publications
(513 citation statements)
references
References 30 publications
25
481
3
4
Order By: Relevance
“…Addressing the implications of resistance should make it possible to determine if virologic failure in the face of CCR5 antagonist therapy will affect viral tropism and disease progression in any meaningful way. Passaging HIV-1 in the presence of increasing concentrations of a CCR5 antagonist in vitro can result in the development of mutations in Env that enable it to recognize the drugbound conformation of CCR5 (22,33,51,56). A similar resistance pathway can occur in vivo or, as we have shown, can even occur in the absence of drug selection (48,53).…”
Section: Discussionmentioning
confidence: 78%
See 3 more Smart Citations
“…Addressing the implications of resistance should make it possible to determine if virologic failure in the face of CCR5 antagonist therapy will affect viral tropism and disease progression in any meaningful way. Passaging HIV-1 in the presence of increasing concentrations of a CCR5 antagonist in vitro can result in the development of mutations in Env that enable it to recognize the drugbound conformation of CCR5 (22,33,51,56). A similar resistance pathway can occur in vivo or, as we have shown, can even occur in the absence of drug selection (48,53).…”
Section: Discussionmentioning
confidence: 78%
“…A similar resistance pathway can occur in vivo or, as we have shown, can even occur in the absence of drug selection (48,53). This resistance pathway often, but not always, results in a virus that is resistant to multiple CCR5 antagonists (22,33,39,53,56). The CCR5 antagonists that have been used clinically all seem to bind to a hydrophobic region in the transmembrane helices of CCR5 and induce conformational alterations in the extracellular domains of the coreceptor that inhibit recognition by gp120 (13,31,32,46,52).…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…[30] In addition, it has been reported that laboratory adapted maraviroc-resistant HIV mutants can still bind to the coreceptor while maraviroc is bound to CCR5, suggesting that the virus binding site and the maraviroc binding site are independent of each other and that maraviroc works by an allosteric mechanism. [31] Since its approval, maraviroc has shown to be very effective in patients carrying R5 tropic HIV and has shown little occurrence of maraviroc resistant HIV strains. However, maraviroc produces an immunomodulary effect characterized by an increase in CD8þ T-cells, of which the effect of long term use has not yet been determined.…”
Section: Entry Inhibitorsmentioning
confidence: 99%